Nyalasé and Ecological Awareness: Qur’anic Values and Local Wisdom in Madura - Fitrian, Zaglul; Nailun Najah; Ita Wulan Sari (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
Nyalasé is a grave pilgrimage tradition that has long been an integral part of the religious life of the Madurese community. Although previous studies have examined this tradition from anthropological and religious ritual perspectives, its ecological dimension and its relationship with Qur’anic values have received little scholarly attention. This study aims to analyze the relationship between Qur’anic values and local wisdom embedded in the Nyalasé tradition and to explore its contribution to the development of ecological awareness among the Madurese people. The study employs a phenomenological approach and a descriptive qualitative method. Data were collected through field observations, in-depth interviews with religious and community leaders, and a review of Qur’anic tafsir literature and Islamic ecotheology. The findings reveal that the Nyalasé tradition reflects Qur’anic values that emphasize respect for all of Allah’s creation, human responsibility as khalifah in preserving the environment, and the harmonization of relationships between humans and nature. These values are internalized through the community’s socio-religious practices, fostering an ecological awareness rooted in local culture. This study contributes to the development of Living Qur’an studies and Islamic ecotheology by demonstrating that grave pilgrimage traditions can function as a medium for internalizing Qur’anic values that support environmental conservation. The findings affirm that Nyalasé represents a manifestation of ecological spirituality grounded in local wisdom within the Madurese community.